Fluid resuscitation-related coagulation impairment in a porcine hemorrhagic shock model - Alexander Ziebart; Robert Ruemmler; Christian Möllmann; Jens Kamuf; Andreas Garcia-Bardon; Serge C. Thal; Erik K. Hartmann (PeerJ, 2020)
Background Fast and effective treatment of hemorrhagic shock is one of the most important preclinical trauma care tasks e.g., in combat casualties in avoiding severe end-organ damage or death. In scenarios without immediate availability of blood products, alternate regimens of fluid resuscitation represent the only possibility of maintaining sufficient circulation and regaining adequate end-organ oxygen supply. However, the fluid choice alone may affect the extent of the bleeding by interfering with coagulation pathways. This study investigates the impact of hydroxyethyl starch (HES), gelatine-polysuccinate (GP) and balanced electrolyte solution (BES) as commonly used agents for fluid resuscitation on coagulation using a porcine hemorrhagic shock model. Methods Following approval by the State and Institutional Animal Care Committee, life-threatening hemorrhagic shock was induced via arterial blood withdrawal in 24 anesthetized pigs. Isovolumetric fluid resuscitation with either HES, GP or BES (n = 3 × 8) was performed to compensate for the blood loss. Over four hours, hemodynamics, laboratory parameters and rotational thromboelastometry-derived coagulation were analyzed. As secondary endpoint the porcine values were compared to human blood. Results All the agents used for fluid resuscitation significantly affected coagulation. We measured a restriction of laboratory parameters, clot development and clot firmness, particularly in HES- and GP-treated animals. Hemoglobin content dropped in all groups but showed a more pronounced decline in colloid-treated pigs. This effect was not maintained over the four-hour monitoring period. Conclusion HES, GP, and BEL sufficiently stabilized the macrocirculation, but significantly affected coagulation. These effects were most pronounced after colloid and particularly HES administration. Despite suitability for rapid hemodynamic stabilization, colloids have to be chosen with caution, because their molecular properties may affect coagulation directly and as a consequence of pronounced hemodilution. Our comparison of porcine and human coagulation showed increased coagulation activity in pig blood.